Using sensors in precision crop production - Schmidt, Rezső; Mogyorósi, Barbara; Gergely, István (Acta Agraria Debreceniensis, 2012)
Proper plant nutrition that takes into consideration both the requirements of plants and ecological conditions is one of the most important precondition of successful plant production. An important element of the N-fertilization of wheat is that the optimum zone of nitrogen supply is significantly narrower than that of other plant species, therefore it can easily happen that we apply higher or lower nitrogen doses than the optimal one. A possible solution to this problem can be precision agriculture. Applying the methods of precision agriculture we can take into consideration the heterogeneity of fields. By applying precision methods either online or offline we can intervene faster than if we would rely only on regular soil and plant analysis procedures. The determination of the doses of nitrogen and the timing of application are influenced also environmental andeconomic aspects. The chlorophyll content of the leaves indicates the nitrogen status of plants, since there is a relationship between the nitrogen content and the amount of chlorophyll in the leaves. According to plant analysis results there was a strong and significant relationship between the values of the NDVI (Normalized Difference Vegetation Index)and the total nitrogen content measured in the leaves.